Educação ambiental e EJA: discutindo conceitos científicos a partir da poluição dos rios numa perspectiva interdisciplinar - Silva, Cleiziane Cruz da (Brasil, 2024)
The present study aimed to analyze the learning of scientific concepts through an interdisciplinary approach, centered on the theme of river pollution. Twenty-seven EJA students from a public school in Itacoatiara-AM participated in the study, using a questionnaire and activity sheets as data collection instruments. The interdisciplinary approach was essential, combining elements of Chemistry and Biology to facilitate the understanding of the interactions between different disciplines. In terms of results, the students demonstrated an initial understanding of the sources of pollution and their impacts, but had difficulty explaining more complex concepts such as density and the relationship between mass and volume. Through the experiment, it was possible to observe progress in learning, with the students being able to identify and describe the materials used and the phenomena observed. This pedagogical proposal proved to be effective in promoting meaningful learning, encouraging students to reflect on the environmental challenges of the environment in which they live and to develop practical solutions to reduce the impacts of pollution. The interdisciplinary approach and the contextualization of content are essential for efficient environmental education, capable of forming critical and responsible citizens.